The Day the Solar Wind Disappeared at Mars - Halekas, J. S. (2023)
In December 2022, an extremely low-density solar wind stream encountered first the Earth and then Mars, shortly after the radial alignment of the two planets (i.e., Mars opposition). As the low-density stream passed Mars, the properties of the Mars-solar wind interaction changed dramatically in response to the low solar wind Alfvénic Mach number and dynamic pressure. The Martian magnetosphere and its boundaries expanded by thousands of kilometers, extending outside of the nominal average bow shock location. The low upstream Mach number resulted in a low ratio of plasma to magnetic field pressure in the magnetosheath, allowing the formation of a very high but stable ion temperature anisotropy, together with a very low level of electromagnetic instabilities. Meanwhile, the decrease in solar wind dynamic pressure caused the Martian upper ionosphere at the terminator to transition from a magnetized state to an unmagnetized state. This event provides an opportunity to study a unique end-member state of the Mars-solar wind interaction.